2022
DOI: 10.3389/fnhum.2022.955238
|View full text |Cite
|
Sign up to set email alerts
|

Inter-brain plasticity as a biological mechanism of change in psychotherapy: A review and integrative model

Abstract: Recent models of psychopathology and psychotherapy highlight the importance of interpersonal factors. The current review offers a biological perspective on these interpersonal processes by examining inter-brain synchrony—the coupling of brain activity between people interacting with one another. High inter-brain synchrony is associated with better relationships in therapy and in daily life, while deficits in the ability to achieve inter-brain synchrony are associated with a variety of psychological and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…The longitudinal approach corresponds with the temporal dynamics of aesthetic experiences that change over time (Aleem & Grzywacz, 2023;Brielmann et al, 2024;Starr, 2023b). Indeed, hyperscanning research on parent-child, youth-elderly, therapist-patient social interactions, which weave in behavioral/psychological observations can address the need and potential for longitudinal designs (Moffat et al, 2024;Russo & Senese, 2023;Sened et al, 2022Sened et al, , 2022bTurk et al, 2022). The use of MoBI in a hyperscanning setting is at the forefront of advancing our understanding of the complex interaction between the brain, body, the environment, and social behavior (Crasso-Cladera et al, 2024).…”
Section: Present and Future Research On The Neuroscience Of Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longitudinal approach corresponds with the temporal dynamics of aesthetic experiences that change over time (Aleem & Grzywacz, 2023;Brielmann et al, 2024;Starr, 2023b). Indeed, hyperscanning research on parent-child, youth-elderly, therapist-patient social interactions, which weave in behavioral/psychological observations can address the need and potential for longitudinal designs (Moffat et al, 2024;Russo & Senese, 2023;Sened et al, 2022Sened et al, , 2022bTurk et al, 2022). The use of MoBI in a hyperscanning setting is at the forefront of advancing our understanding of the complex interaction between the brain, body, the environment, and social behavior (Crasso-Cladera et al, 2024).…”
Section: Present and Future Research On The Neuroscience Of Catsmentioning
confidence: 99%
“…Increased INS has also been linked to feelings of shared intentionality, positive beliefs in cooperativity, perceived social closeness (Dikker et al, 2017) and social behavior, that is, joint action and eye contact (Dikker et al, 2021). Since many forms of psychopathology are associated with a reduced ability to achieve INS in various contexts, it was suggested as a neurobiological mechanism underlying plastic change in psychotherapy (Sened et al, 2022b). Indeed, INS between patient and therapist, shaped by the embodied and relational aspects, has been associated with work alliance in psychological counseling (Zhang et al, 2018), and has been proposed as a neurobiological mechanism to infer the other’s inner states and facilitate mutual understanding and emotional exchange (Koole & Tschacher, 2016).…”
Section: Interactive Relational Aesthetic Experiences At the Core Of ...mentioning
confidence: 99%
“…Elucidating the mechanisms underpinning joint action may have an impact in a variety of social contexts involving mates, colleagues, competitors, genders, up to the understanding and improvement of decision-making mechanisms (Oullier and Basso, 2010;Krueger and Meyer-Lindenberg, 2019). The comprehension of the neurophysiological underpinnings of joint action may affect the development of best practices in the medical field (Leong et al, 2021;Short et al, 2021;Sened et al, 2022;Tucek et al, 2022) and in school teaching (Bevilacqua et al, 2019), it may help optimizing leadership processes or employees' cooperativeness in corporate life (Astolfi et al, 2015;Zhang et al, 2019;Balconi et al, 2020;Boukarras et al, 2022), or it may support the improvement of sport performance (Filho et al, 2016;Cassani et al, 2020;Filho and Tenenbaum, 2020;Gugnowska et al, 2022). Knoblich and Jordan (2002) were the first to hypothesize that human joint actions should be sustained by the activity of specific brain structures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, efforts have been made to assess alliance from a variety of measures directly recorded during therapy sessions such as patient-clinician language use, 4 , 5 head and body movements, 6 facial expressions, 7 respiration rate and heart rate variability, 8 and brain activities. 9 , 10 These studies have found initial evidence that the behavioral and physiological synchrony between patients and therapists during sessions can be measured as a proxy of alliance. 4 , 6 , 7 , 8 , 9 To be clinically actionable, however, data-driven approaches must identify what specific behavioral features clinicians can pay attention to and potentially adjust to optimize alliance during therapy.…”
Section: Introductionmentioning
confidence: 99%